Application of jigsaw cooperative learning type based on socio-scientific issues to improve argumentation skills on nervous system material - Mardiyah, Fitri Husni; Suhara, Suhara; Gemilawati, Meilia (Department of Biology Education, Universitas Pendidikan Indonesia, 2024)
The use of a jigsaw type cooperative learning model based on socioscientific issues in nervous system material can be used as a way to provide students with argumentation skills. This research aims to obtain information regarding the application of jigsaw type cooperative learning based on socioscientific issues in improving students' argumentation skills regarding the nervous system. This research uses classroom action research methods. The sample in this study was class XI students consisting of 36 people. The results of this research show that there is a significant difference in the average between before and after action research in argumentation skills. In cycle 1, the pretest score achieved argumentation level 1 (score 64.36), while in the posttest score achieved argumentation level 2 (score 72.75). After treatment in cycle 2, namely the application of jigsaw type cooperative learning based on socioscientific issues, it was able to improve students' argumentation skills. The posttest score achieved argumentation level of 3 (score 76.17) becomes a score of 80.39 with an argumentation level of 4. So, based on this classroom action research, the application of jigsaw type cooperative learning based on socioscientific issues and improves students' argumentation skills in nervous system material.